Analisis Kemampuan Komunikasi Matematis : Dampak Model Pembelajaran Discovery Learning Terintegrasi Learning Start With A Question - Setiaji, Fahkur; Suherman, Suherman; Kuswanto, Eko (Universitas Islam Negeri Raden Intan Lampung, 2019)
The purpose of this study is to determine the effect of the discovery learning model integrated learning start with a question of mathematical communication skills. This research is a quantitative research with a type of quasi experiment. The sampling technique in this study is the random sampling technique. Data collected through interview observation and test. The data analysis technique used is the uncorrelated t test. Based on the results of research and data processing, it was found that there was an influence of discovery learning integrated learning model start with a question and discovery learning learning model on mathematical communication skills. Furthermore, mathematical communication of students by using the discovery learning model integrated learning start with a question is better than mathematical communication of students using discovery learning learning models.